Pengaruh Literasi Keuangan Dan Pemanfaatan Financial Technology Terhadap Kepatuhan Pajak Pebisnis Online Yang Dimoderasi Digitalisasi Perpajakan - Calista Ayu Millenia Risti; Rio Johan Putra (Politeknik Ganesha Medan, 2022)
Online businesses have the same activities as conventional businesses, namely managing businesses with the aim of making profits, so online businesses are required to pay taxes as stated in Undang-undang No.7 Tahun 2021 concerning Harmonization of Tax Regulations (HPP). The purpose of this study is to analyze the effect of financial literacy and financial technology utilization on tax compliance which is moderated by tax digitalization on online business owner in Jabodetabek. This study uses a quantitative approach with a associative research design. Data collection in this study was carried out by distributing questionnaires given to 150 people who are online business owner in the Jabodetabek area. The analytical techniques used to answer the hypothesis in this study are multiple linear regression analysis and Moderated Regression Analysis (MRA) test. The analysis result shows that financial literacy has no significant effect on tax compliance, financial technology utilization has a positive and significant effect on tax compliance, tax digitalization is not able to moderate the effect of financial literacy on tax compliance, and tax digitalization is able to moderate by strengthening the influence of financial technology utilization on tax compliance.